Current Problems in the Field of Sickness Insurance for People Running a Non-Agricultural Business - Matyjas-Łysakowska, Paulina (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The assessment of the limits of the freedom to declare the basis for calculating the contribution for sickness insurance by the insured (entrepreneur) constantly raises legal doubts. The social security authority verify, often successfully, the correctness and reliability of the declared contribution even if the insured declares the basis within the limits provided for by law. The action of the authority reduces the basis for declared contributions and, as a result, affects the amount of benefits. Doubts regarding the assessment of the possibility of veryfing the declared basis for contributions revolve around the assessment of whether in this respect we are dealing with a legal gap in social security law or with a comprehensive regulation of the autonomous social security law. In the context of the analyzed issue, it is crucial to establish the relationship between social security law and civil law and to indicate the grounds for separating social security law as an autonomous branch of law.